PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP DENGAN MENGGUNAKAN MODUL GEOMETRI RUANG BERBASIS PROBLEM BASED LEARNING - Rina Febriana; Hafizah Delyana; Radhya Yusri (Universitas Muhammadiyah Malang, 2020)
The teaching materials used are also still text books provided by schools. Students are not familiar with contextual questions. To create such a learning process and be able to develop the potential that exists in students, the teaching material developed is a module based on Problem Based Learning (PBL) on Geometry learning Space. The use of appropriate learning media can help students learn and understand the material, so that teachers are expectedto know the meaning and function of a media, get to know as much as possible the media that can be used, choose media that is suitable for the subject matter, can or can use, store and maintain even no less important is the ability of teachers to plan and create their own learning media that can help students understand abstract concepts. To help teachers develop and create mathematics learning media that can improve students' understanding of concepts, learning media are needed that can be used to help students explore material. By Karen, it is necessary to carry out community service activities in the form of Socialization of the Use of Problem Based Learning Geometry Modules in Class IX Students of Adabiah.